2017
DOI: 10.1111/hae.13349
|View full text |Cite
|
Sign up to set email alerts
|

Describing the quality of life of boys with haemophilia in China: Results of a multicentre study using the CHOKLAT

Abstract: Introduction The treatment of haemophilia varies across countries and across regions within some countries. Similar variation has been observed in health‐related quality of life (HR‐QoL). Relatively little is known about the HR‐QoL of boys with haemophilia in China. Aim The aim of this study was to describe the HR‐QoL of boys with haemophilia in China using the Canadian Haemophilia Outcomes‐Kids Life Assessment Tool (CHO‐KLAT). Methods Boys (4‐18 years of age) with haemophilia and their parents were enroled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Mean value of CHO-KLAT parent proxy reports (64.69, SD = 13.71) was similar to child self-reports (65.33, SD = 15.78) without statistically significant differences. This result is comparable to the study of L. Tang et al in China [16], but the scores were significantly lower than reported scores in developed countries such as Canada [18](75.4, SD = 12.0), Germany (71.5, SD = 13.3), France (76.7, SD = 9.7), Spain (78.4, SD = 10.8) and the Netherlands (82.8, SD = 8.4) [14], where prophylaxis is taken as the standard treatment of haemophilia with severe haemophilia. This difference indicates that economic development may have a considerable effect on the QoL of haemophilia.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Mean value of CHO-KLAT parent proxy reports (64.69, SD = 13.71) was similar to child self-reports (65.33, SD = 15.78) without statistically significant differences. This result is comparable to the study of L. Tang et al in China [16], but the scores were significantly lower than reported scores in developed countries such as Canada [18](75.4, SD = 12.0), Germany (71.5, SD = 13.3), France (76.7, SD = 9.7), Spain (78.4, SD = 10.8) and the Netherlands (82.8, SD = 8.4) [14], where prophylaxis is taken as the standard treatment of haemophilia with severe haemophilia. This difference indicates that economic development may have a considerable effect on the QoL of haemophilia.…”
Section: Discussionsupporting
confidence: 90%
“…The concept of HRQoL was raised decades ago in haemophilia [710], and recent research outcomes emphasize the importance of considering HRQoL issues during decision making procedures surrounding the treatment of haemophilia [1116]. HRQoL assessment provides a comprehensive vision of the patients’ subjective feelings of function and well-being, and supports evaluation of therapeutic effect [10, 13, 16]. The Canadian Haemophilia Outcomes–Kids’ Life Assessment Tool (CHO-KLAT) is a well-known disease-specific measure of HRQoL for childhood haemophilia patients [8, 17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] In studies including Chinese patients, most of them only focused on specific groups such as children or patients with inhibitors. 15,16 Only one study in 2004 investigated the quality of life of the Chinese adults with haemophilia and compared it with that of the general population. 17 This study demonstrated PwH experienced significantly lower levels of HRQoL compared with the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The HRQoL among PwH has been previously studied in several countries, such as the US, Brazil, Iran, Korea and Sweden 10–14 . In studies including Chinese patients, most of them only focused on specific groups such as children or patients with inhibitors 15,16 . Only one study in 2004 investigated the quality of life of the Chinese adults with haemophilia and compared it with that of the general population 17 .…”
Section: Introductionmentioning
confidence: 99%